HDAC1 Regulates Neuronal Differentiation - Nieto-Estevez, Vanesa; Changarathil, Gopakumar; Adeyeye, Adebayo Olukayode; Coppin, Marissa Olga; Kassim, Rawan Serena; Zhu, Jingfei; Hsieh, Jenny (Frontiers in Molecular Neuroscience, 2022)
In adult hippocampal neurogenesis, chromatin modification plays an important role in neural stem cell self-renewal and differentiation by regulating the expression of multiple genes. Histone deacetylases (HDACs), which remove acetyl groups from histones, create a non-permissive chromatin that prevents transcription of genes involved in adult neurogenesis. HDAC inhibitors have been shown to promote adult neurogenesis and have also been used to treat nervous system disorders, such as epilepsy. However, most HDAC inhibitors are not specific and may have other targets. Therefore, it is important to decipher the role of individual HDACs in adult hippocampal neurogenesis. HDACs 1, 2, and 3 have been found expressed at different cellular stages during neurogenesis. Conditional deletion of HDAC2 in neural stem cells impairs neuronal differentiation in adult hippocampus. HDAC3 supports proliferation of adult hippocampal neural stem/progenitor cells. The role of HDAC1 in adult neurogenesis remains still open. Here, we used a conditional knock-out mouse to block HDAC1 expression in neural stem cells (Nestin+ cells) during hippocampal neurogenesis. Our results showed that both HDAC1 and HDAC2 are expressed in all cellular stages during hippocampal neurogenesis. Moreover, we found that deletion of HDAC1 by viral infection of neural stem cells is sufficient to compromise neuronal differentiation in vitro. However, we were unable to reduce the expression of HDAC1 in vivo using Nestin-CreERT2 mice. Understanding the role of HDAC1 may lead to ways to control stem cell proliferation and neuronal regeneration in the adult hippocampus, and to more specific HDAC therapeutics for neurological disorders.